2013
DOI: 10.1149/2.015311jes
|View full text |Cite
|
Sign up to set email alerts
|

Electrosynthesis of Ti2COnfrom TiO2/C Composite in Molten CaCl2: Effect of Electrolysis Voltage and Duration

Abstract: Ti2COn powders with controllable oxygen contents have been successfully synthesized by electro-reduction of solid TiO2-graphite composite precursors in molten CaCl2. The effect of electrolysis time and applied cell voltage on the carbon and oxygen content of the product was systematically investigated. The reduction pathway of the composite electrode was studied based on the analysis of intermediate products using X-ray diffraction (XRD), scanning electron microscopy (SEM) and X-ray photoelectron spectroscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…The curve reveals that the current decreases rapidly within the initial 2 h and then declines slowly to a stable level (around 0.45 A) until the electrolysis is terminated. Electrodeoxidation generally occurs from the outside to the inside of the cathodic pellet, and the preferentially generated products, such as TiC x O y , may accelerate the reduction due to their good conductivities . As the reaction proceeds and the removal of oxygen ions continues, the reduction speed of the pellet becomes slower and the current is relatively stable during the later electrolysis period (10–20 h).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The curve reveals that the current decreases rapidly within the initial 2 h and then declines slowly to a stable level (around 0.45 A) until the electrolysis is terminated. Electrodeoxidation generally occurs from the outside to the inside of the cathodic pellet, and the preferentially generated products, such as TiC x O y , may accelerate the reduction due to their good conductivities . As the reaction proceeds and the removal of oxygen ions continues, the reduction speed of the pellet becomes slower and the current is relatively stable during the later electrolysis period (10–20 h).…”
Section: Resultsmentioning
confidence: 99%
“…Electrodeoxidation generally occurs from the outside to the inside of the cathodic pellet, and the preferentially generated products, such as TiC x O y , may accelerate the reduction due to their good conductivities. [39,40] As the reaction proceeds and the removal of oxygen ions continues, the reduction speed of the pellet becomes slower and the current is relatively stable during the later electrolysis period (10-20 h). After 20 h electrolysis, the total charge flowing through the electrolytic cell is %9.56 Ah.…”
Section: Variations Of the Phase Composition Current And Morphology During Electrodeoxidation Processmentioning
confidence: 99%
“…This can be a disadvantage if rening is required but can be a considerable advantage if alloys are desired especially those that are difficult to make when the melting point of one element is greater than the boiling point of some of the other alloying elements. A very large number of alloys and intermetallic compounds have been made including TiNi, [45][46][47] TiMo, 48 TiW, 49 Al 3 Sc, 50 NbAl, 51 NiTiHf, 52 TaNb, 53 NbHf, 54 HfC, 55 Ti 2 CO, 56 TiSi, 57 LaNiCo, 58 TaC 59 and TiC/SiC composite. 60 At the present time, the process is being developed by Metalysis Ltd (http:// www.metalysis.com) in the UK concentrating on tantalum powder for capacitors and titanium powders for near net shape processing.…”
Section: Titaniummentioning
confidence: 99%
“…Molten salt electrolysis provides a convenient and fairly easy way to obtain carbide materials. It was reported that MCxOy and MCx have been synthesized by electrolysis using the mixture of MO2 and C as precursor in molten chloride [19,[21][22][23][24][25][26]. Electrolytic synthesis of MCxOy is a process of removing O 2from MOx and carbon complexes.…”
Section: Introductionmentioning
confidence: 99%